Guidelines for the Treatment of Urinary Incontineence and Overactive Bladder - C.F. Heyns; G.W. Rienhardt (South African Family Practice)
Urinary incontinence (UI) is the involuntary leakage of urine, while overactive bladder (OAB) is characterised by frequency, nocturia and urgency, with or without incontinence. This paper provides guidelines for the management of UI and OAB, focusing on primary health care. Although UI and OAB negatively impact on the patients quality of life more severely than diabetes mellitus or rheumatoid arthritis, surveys have shown that more than 60% of persons with UI never mention their problem to a doctor or nurse.Therefore, the primary care setting is ideal for screening, basic evaluation, and initial management of UI and OAB. A focused history and examination will usually enable the practitioner to distinguish between the different types of incontinence, such as stress, urge (overactive bladder), mixed, overflow and continuous incontinence. It should include a vaginal examination and cough test in women, rectal examination in men, dipsticks urinalysis, and assessment of the post-void residual urine. A bladder diary filled in by the patient can be very useful. There may be reversible conditions causing or contributing to the patients incontinence, such as urinary tract infection. In certain cases referral to a specialist is required, e.g. patients with incontinence after previous surgery, or associated with pain or hematuria. However, many patients with symptoms of OAB or UI can be eff ectively treated at the primary care level. Management options include lifestyle modification (e.g. smoking cessation and weight loss), pelvic floor exercises, and pharmacotherapy. Overactive bladder can be treated with muscarinic antogonists such as tolterodine and oxybutinin.